The structure of the anaerobic thermophilic microbial community for the bioconversion of the cellulose-containing substrates into biogas. (March 2018) - Tsavkelova, Elena; Prokudina, Ljuba; Egorova, Maria; Leontieva, Maria; Malakhova, Dina; Netrusov, Alexander
Graphical abstract: Highlights: Thermophilic wastepaper-degrading microbial community (MC) was studied. Ruminiclostridium ( Clostridiales ) dominates in the paper-degrading thermophilic MC. Syntrophic acetate oxydizers and hydrogenotrophic methanogens constitute the MC. The mixture of different papers facilitates the bioconversion of the hard ones. Abstract: The structure of the microbial community digesting various waste papers under the thermophilic (55 °C) conditions was analyzed by a multilateral approach, comprising the denaturing gradient gel electrophoresis (DGGE) and the high-throughput sequencing (HTS), supported by the light- and scanning electron microscopy (SEM). The most abundant and diverse microbial populations were observed when the office paper, corrugated carton and the waste paper mixture were used, whereas the poorest communities were detected on the magazine paper and newspaper. These results were also confirmed by the DGGE analysis. Within Bacteria, the main groups were affiliated to Firmicutes ( Acetivibrio, Herbinix, Thermoanaerobacterium, Tepidanaerobacter ). Bacteria, identified as Acetivibrio cellulolyticus, due to the comparative analysis within databases, belong to the genus Ruminiclostridium. Methanothermobacter and Methanosarcina were among the dominant Archaea . The HTS analysis showed the high prevalence of Clostridia ( Ruminiclostridium ). The representatives of all the trophic groups, needed for an efficient bioconversion of the wastepaper into the biogas, were detected by HTS as well, including diverse hydrolytics and fermentative species. The presence and amount of the syntrophic acetate-oxidizing bacteria Tepidanaerobacter and Thermoanaerobacterium, and their tight association with the hydrogenotrophic methanogens, are discussed concerning the completeness and effectiveness of the bioutilization of different types of non-pretreated papers.